Genome characterization of piscine ‘Scale drop and Muscle Necrosis syndrome’-associated strain of Vibrio harveyi focusing on bacterial virulence determinants - P. Kayansamruaj (2019)
© 2017 The Society for Applied Microbiology Aims: Genomic characterization of Harveyi clade vibrio strain Y6 causing ‘Scale drop and Muscle Necrosis syndrome’ (SDMN) isolated from barramundi (Lates calcarifer) in Vietnam. Methods and Results: A bacterial genome was sequenced using Illumina MiSeq platform. Multilocus sequence analysis confirmed that the bacterium belongs to Vibrio harveyi species. Further phylogenetic analysis inferred from core genome SNPs revealed a close relationship between our bacterium and the V. harveyi isolated from groupers in Taiwan and China. blastp results indicated that V. harveyi piscine strains carried numerous adhesin, secretion system, siderophore and toxin-related genes. Genome comparison between Y6 and 32 strains of V. harveyi from different origins showed that at least 17 potential virulence genes were present exclusively in the strain Y6. Many of these (six of 17 genes) were homologous to pyoverdine siderophore, a secreted high-affinity iron chelator, clusters originally found in Pseudomonas aeruginosa. Genome of V. harveyi Y6 was incorporated by a bacteriophage VHY6φ and replication protein of the phage was most similar to CTXφ described previously in Vibrio cholerae and Vibrio fischeri. However, the cholera toxin-encoding genes, namely ctxA and ctxB, were absent from VHY6φ, while the CTXφ-enterotoxin gene (zonula occludens toxin; zot) remained intact. Conclusions: Several putative virulence genes and a phage carrying toxin gene were identified in the genomes of SDMN-associated V. harveyi Y6. Significance and Impact of the Study: This study confers genomic information of the piscine pathogenic V. harveyi which recently caused widespread mortality. Such information is of importance to gain insight into bacterial molecular pathogenesis.